Frequency of Thyroid Dysfunction and Congenital Heart Defects in Subjects with Down Syndrome - Erum Afzal, Muhammad Sohail Arshad, Waqas Imran Khan (Journal of Rawalpindi Medical College, 2021)
ABSTRACT: Background: Down syndrome (DS) is the most common chromosomal abnormality with prevalence of 1 in 700-1500 live births. Its manifestations may include congenital heart defects(CHD), thyroid dysfunctions, hematopoietic disorders, early-onset Alzheimer disease, gastrointestinal disorders, neuromuscular weakness, hearing and visual problems, characteristic facial and physical features. The prevalence of thyroid disorders and congenital heart diseases are higher in DS patients than in general population. Objective:To explore the frequency, and types of congenital heart defects (CHD) and Thyroid disorders in children with Down syndrome (DS) in the children hospital and the institute of child health (CHICH) Multan. Study design: Descriptive cross sectional Setting: Outpatient department (OPD) of CHICH Multan Method:A total of 158 down syndrome (DS) patients of 0 to 15 years of age, of both genders were included in this study from October 2019 to October 2020. DS was diagnosed by specific clinical features and karyotyping. Age, sex and mother’s age was noted. Blood samples of all the patients were sent for karyotyping and serum T4 and Thyroid stimulation hormone (TSH). For patients more than 36 months, blood samples were also sent for Antithyroglobulin and antithyroid peroxidase antibodies. Echocardiography of all the patients was done. Data was collected and analyzed by using SPSS version 16.0. Results:Out of 158 DS children most presented below 6months of age, with male to female ratio of 1:1.4. Mostly mothers were between 20 to 40 years of age. Karyotyping revealed non disjunction in 97% of cases. Cardiac abnormalities were found in 48% of DS children. Most common Type was VSD (10.9%), Thyroid abnormalities were detected in 24% of DS patients, subclinical hypothyroidism (13.9%) was most common. Conclusion: CHD and Thyroid disorders must be ruled out in all DS patients,to start early management. Keywords: Down syndrome, Congenital heart disease, hypothyroidism.